Friday

July 25, 2014

July 25, 2014

Posted by **madi** on Wednesday, January 19, 2011 at 6:37pm.

- algebra 2 -
**Reiny**, Wednesday, January 19, 2011 at 7:47pmthere is a fast way to do this using the property

if

ax^2 + bx + c = 0, then

sum or roots = -b/a

product of roots = c/a

sum of roots = (4+3i) + (4-3i) = 8

product of roots = (4+3i)(4-3i) = 16-9 = 7

equation:**x^2 - 8x + 7 = 0**

another way is to form the factors:

(x - (4+3i)) and (x - (4-3i)) and set

(x - (4+3i))(x - (4-3i)) = 0

(x - 4 - 3i)(x - 4 + 3i) = 0

carefully expand, simplify and you will get the above answer.

**Related Questions**

Algebra - Given the roots, 1/2 and 4, find: (A) The quadratic equation 2x^2-9x+4...

Algebra 2 - How do I solve this quadratic function by finding square roots 2x²=...

Math (Algebra) - If the ratio of the roots of the quadratic equation x^2−...

ALGEBRA 2 PLEASE HELP - How do I solve this quadratic function by finding square...

Algebra - Find the number of integer quadruples (a,b,c,d) with 0\leq a,b,c,d \...

Algebra - Find the number of integer quadruples (a,b,c,d) with 0\leq a,b,c,d \...

math - I'm having trouble understanding one step in a proof of the Cauchy-...

college math - apply the quadratic formula to find the roots of the given ...

college math - apply the quadratic formula to find the roots of the given ...

College Algebra - Let g(x) = -2x2 + bx + c be a quadratic function, defined ...